Pengembangan Landmark dan Agrowisata Cokelat (Studi Kasus Desa Banjarharjo, Kecamatan Kalibawang) - Krismiyanto, MT., Ir. Yoseph Dwikora (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) is an action used by the student to do community services. Community services have a goal to increase the potency that is owned by a region. Through the  action of KKN 79, Group 23 has a program to develop the potency of Desa Banjarharjo, Kecamatan Kalibawang, Kabupaten Kulon Progo. Desa Banjarharjo is a village that has a high potency of chocolate, but that potential is not fully utilized. Because of that, Group 23 research to develop the village potential. The research is done with secondary data collected from the internet. This is due to the limited conditions caused by the pandemic so that direct data collection is not possible. Based on the data that have been collected, the result is a program to make a landmark of the village for the village’s identity and the development of chocolate agrotourism. The program is supported by the marketing guide, legality guide, taxation guide, development of the chocolate product, and village’s branding that can be found in KKN Buku Saku.